ANALISIS WACANA VAN DIJK TERHADAP ANIMASI RELIGI “NEGARA ISLAMI” (KARYA CISFORM UIN SUNAN KALIJAGA & PPIM UIN JAKARTA) - Malik, Rifâ€™atul Khoiriah (Komodifikasi, 2019)
The concept of khilafah which became a debate among the public triggered several conflicts in Indonesia. This concept does not escape the system of government of the country. If you look back at the history of Islam where the Prophet Muhammad held the "Medina Charter", then the glory of Islam at that time did not escape from a just government without seeing the religion adopted. Therefore religious animation "Islamic State" created by CISform and PPIM became education and provided an overview of the current Indonesian government. From here arises several questions. What is the ideology behind making religious animations "Islamic State"? Is religious animation "Islamic State" able to reduce radical information that is increasingly prevalent in online media? This research is complemented by the opinions of leaders about the Islamic State. Likewise with the understanding of the basic meaning of khilafah. Through religious animation "Islamic State", they have the aim of counteracting radicalism in society. So that the conclusions from this study are based on the theoretical framework used.